Presidential commission on flood risk management delegate information : 5 February 2002, Institution of Civil Engineers, London, UK. (Thomas Telford, 2002)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of the presidential commission held at ICE, London 5 February 2002.